Nannoniite, Al2(OH)5F, a new mineral from the Cetine di Cotorniano mine (Tuscany, Italy) - C. Biagioni; C. Biagioni; E. Mugnaioli; E. Mugnaioli; S. Lorenzon; D. Mauro; D. Mauro; S. Musetti; J. Sejkora; D. Belmonte; N. Demitri; Z. Dolníček (European Journal of Mineralogy)
The new mineral nannoniite, Al2(OH)5F (Z=4), has been discovered in the Cetine di Cotorniano mine, Chiusdino, Siena, Tuscany, Italy. It occurs as spherical aggregates formed by micrometre-sized crystals, colourless to white in colour, with a white streak and a vitreous to earthy lustre. Fluorescence is bluish-yellow and yellowish-white under short- and longwave UV radiation, respectively. Electron microprobe analysis gave (in wt %) SO3 0.49, Al2O3 63.97, MgO 0.51, CaO 0.22, K2O 0.07, F 11.72, H2O(calc) 28.54, and −O = F −4.94, with a total of 100.58. Nannoniite is monoclinic, with space group P21/n<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="34pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="f46ec57be4c405f29b4061d652d98bf3"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-36-1011-2024-ie00001.svg" width="34pt" height="14pt" src="ejm-36-1011-2024-ie00001.png"/></svg:svg> and with a=8.688(3), b=5.024(2), c=9.734(4) Å, β=90.77(2)°, and V=424.9(3) Å3. The crystal structure was solved using three-dimensional electron diffraction and refined to R(obs)=0.1524 for 2141 unique reflections with I>3σ(I). Nannoniite is homeotypic with gibbsite. In type material, nannoniite is associated with quartz, baryte, gypsum, and alunite in vugs of a silicified limestone. Its origin is probably related to the late-stage circulation of (Al,F)-rich fluids within the Sb ore deposit formerly exploited at the Cetine di Cotorniano mine.